Determinants of tourism demand in Malaysia: Evidence from selected Asian countries / Chen Qiyun - Chen , Qiyun (2020)
Tourism brings numerous benefits to Malaysia by filling up the spreads demand from tourists. Aware of the comparative advantage in tourism from the Malaysian government, the tourism industry is treated as an essential factor in boosting the Malaysian economy. This paper investigates the determinants of tourism demand in Malaysia by tourists from selected Asian countries – Singapore, Indonesia, China and Thailand using quarterly data from 2008 through 2018. Panel data technique is employed to analyze the effect of macroeconomic variables such as real GDP per capita, real exchange rate and trade openness on tourist arrivals in Malaysia. The empirical results show that real GDP per capita and trade openness positively affect tourism demand in Malaysia, while the real exchange rate is negatively correlated with the tourism demand. Lastly, the findings of this study provide corresponding policy recommendations to welcome more international tourists and improve the Malaysian tourism sector.